Do Technological Service Encounters Assist or Perplex the User? Exploring the ’Information Richness’ of Web-based Self-Service Technologies - Badra Sandamali Galdolage (New Visions in Science and Technology Vol. 5, 2021)
Rather than depending exclusively on face-to-face interactions, service businesses now offer their services remotely using Self-Service Technologies (SSTs). This trend can be considered as a natural consequence of technology maturity, and it will eventually become the norm for many future service transactions. Customers presently have the option of choosing SSTs or visiting a physical site for service, but humanoid robots are predicted to eventually take the position of customer support employees. Hence, service businesses are responsible for preparing their clients for such a future. Customers typically perform self-service technologies in the absence of the company’s service employees. Therefore, SSTs should provide appropriate directions and instructions to ensure that they operate efficiently and effectively. Customers would be annoyed if SSTs lacked the necessary information to complete their transactions. Thus, the nature of the information would be critical in ensuring the success of online self-service transactions. This study aims to understand the information richness in online-based self-service technologies from the customers’ perspective. Using a qualitative approach, semi-structured interviews were conducted with 25 SST users. The study found seven critical factors that determine the information richness in online-based SST platforms: ’relevance, timeliness, accuracy, clarity, consistency, sufficiency, and simplicity.’ The study advances awareness of the critical nature of information richness in the acceptance of online-based self-service technologies while providing practical guidance to service providers in designing SSTs that contain rich information to support customers’ successful service performance.